Pemanfaatan Batuan Teraltersi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Gunung Kuda the research area is a hill, a part of southern part of Keromong Mountains. It consists of altered rock, which are exploited as building stone with local name as Batu Palimanan. The data were field observation, petrography, chemical and X-ray difraction. Based on those data, the analysis was conducted and it concluded that the altered rock is dacite, which have altered by hydrothermal processes in 2 types. The argilic, that dominantly spread at southern and western area represented by clay-quartz minerals association, while the silisic is spread at eastern and northern area consists of quartz-pyrite minerals association. Based on the quantity of alteration change, the rock is divide into 4 classes, i.e. Low Grade include Fresh and Faintly Weathered, Moderate Grade are Slightly Weathered and Moderately Weathered, Strong Grade are Highly Weathered and part of Completely Weathered, and Very Strong Grade are Completely Weathered and Residual Soil. As building stones there are 2 type of stones, the Polos and the Bermotif. Almost both classes are Low and Moderate and meet the requirement of standard. The standard is chapter 25 and 26 of PUBI isued by Departemen Pekerjaan Umum (1985). Altered-rock as additional material in ceramic can improve the quality of ceramic-product, in this case is roof tile. It can reduce the shrinkage at sun drying from 10% to 8% and from 1,3% to 0,8% after been burned.